2007
DOI: 10.1111/j.1574-695x.2007.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale evaluation of UV reactors' efficacy againstin vitroinfectivity ofCryptosporidium parvumoocysts

Abstract: An experimental protocol was developed to assess the efficacy of two UV reactors (medium-pressure UVaster s , and a low-pressure reactor) on the infectivity of Cryptosporidium parvum oocysts under conditions mimicking small-or mediumsize water distribution units. The protocol included purification of large amounts of viable oocysts from experimentally infected calf feces, pilot spiking, sample concentration and purification after UV radiation, oocyst quantification and in vitro evaluation of oocyst infectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…2002). Oocyst infectivity of HCT‐8 cell cultures was reduced by (log 10 ) 4·92 and more than 4·82 after exposing oocysts to an effective dose of 40 mJ cm −2 in a medium pressure (MP) or a low pressure (LP) reactor, respectively (Entrala et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2002). Oocyst infectivity of HCT‐8 cell cultures was reduced by (log 10 ) 4·92 and more than 4·82 after exposing oocysts to an effective dose of 40 mJ cm −2 in a medium pressure (MP) or a low pressure (LP) reactor, respectively (Entrala et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…(Hijnen et al 2006). In another pilot-scale study in which water passed through low-and medium-pressure UV reactors, irradiation was found effective in reducing oocyst infectivity in vitro (Entrala et al 2007). Studies evaluating oocyst viability using their in vitro excystation capability and ⁄ or uptake of vital dyes suggested that very high UV (up to 8700 mJ cm )2 ) was necessary to achieve a 99% decrease in viable oocysts (Campbell et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional method of evaluating the performance of a UV reactor is to compare the concentrations of pollutants or active microorganisms at the outlet of the reactor with those at the inlet 8–12. There has been considerable effort put into improving this technique by introducing various chemicals and new methods.…”
Section: Introductionmentioning
confidence: 99%